Water Mediation Is Essential to Nucleation of β‐Turn Formation in Peptide Folding Motifs1. Issue 49 (15th October 2013) - Busch, Sebastian; Bruce, Chrystal D.; Redfield, Christina; Lorenz, Christian D.; McLain, Sylvia E.
<x xml:space="preserve">Abstract</x> Water‐mediated bond formation: The structure of the peptide GPG‐NH2 (see picture) has been investigated in aqueous solution to understand the role of water in the formation of a β‐turn. Using a combination of neutron diffraction enhanced by isotopic substitution, NMR spectroscopy, and computer simulations, it was found that water is an essential component to initiate folding in solution.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>